PENERAPAN ARSITEKTUR TEMATIK PADA TAMAN WISATA KULINER DI KABUPATEN LUWU TIMUR - Pranata, Dandi; Rahayu, Irma; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Culinary tourism in Indonesia has grown rapidly and has become a significant attraction for local tourism development. East Luwu Regency possesses a diverse range of local culinary potential that has yet to be fully optimised through well-designed spaces that enhance the visitor experience and local identity. This study aims to design a Culinary Tourism Park using a thematic architecture approach with a contemporary theme, integrating building elements, materials, and landscaping harmoniously. The research employs a qualitative descriptive method, collecting primary data through field surveys to assess site conditions, accessibility, and topography, along with secondary data from literature studies on culinary parks, thematic architecture, and contemporary design. The data are systematically analysed through descriptive synthesis to develop a design concept that maximises functionality, aesthetics, and visitor comfort. The results indicate that the application of contemporary thematic architecture successfully establishes a strong visual identity, interactive visitor experiences, and a harmonious integration of spatial functions, materials, and landscape elements. The Culinary Tourism Park can serve as a local tourism icon while enhancing social interaction and economic potential in East Luwu Regency.